Solanum tuberosum isolate sensitivity to Phytophthora infestans when using three systemic fungicides - Chañag, Harold Andrés; Álvarez, Sandra Lorena; Lagos, Luz Estela; Burbano-David, Diana Marcela (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Phytophthora infestans is the causative agent of one of the most limiting diseases in potato crops (Solanum tuberosum) in the Department of Nariño, causing farmers to intensively use different fungicides, which reach 30% of production costs and are a serious environmental and public health problem. The purpose of this research was to support integrated disease management programs based on the generation of a baseline sensitivity of 20 P. infestans isolates from the Department of Nariño to three commercial fungicides composed of Metalaxyl 8% + Mancozeb 64% , Cimoxanil 6% + Propineb 70% and Fluopicolide 6% + Propineb 66.7%. This study was carried out using the in vitro methodology and five doses on an exponential scale. The results showed a heterogeneous behavior where some isolates showed resistance to the fungicide composed of Metalaxil + Mancozeb, reaching average  EC50 values of 6.67 μg mL-1; while for the fungicides composed of Cimoxanil + Propineb and Fluopicolide + Propineb, there were intermediate and sensitive sensitivity levels with average EC50 values of 1.57 μg mL-1 and 2.61 μg mL-1. On the other hand, the sporulation rate was reduced in its entirety with the three fungicides for the evaluated doses of 100; 1,000; 10,000 μg mL-1.